3D modeling of phytoplankton seasonal variation and nutrient budget in a southern Mediterranean Lagoon. Issue 2 (30th January 2017) - Béjaoui, Béchir; Solidoro, Cosimo; Harzallah, Ali; Chevalier, Cristèle; Chapelle, Annie; Zaaboub, Noureddine; Aleya, Lotfi
Abstract: A 3D coupled physical-biogeochemical model is developed and applied to Bizerte Lagoon (Tunisia), in order to understand and quantitatively assess its hydrobiological functioning and nutrients budget. The biogeochemical module accounts for nitrogen and phosphorus and includes the water column and upper sediment layer. The simulations showed that water circulation and the seasonal patterns of nutrients, phytoplankton and dissolved oxygen were satisfactorily reproduced. Model results indicate that water circulation in the lagoon is driven mainly by tide and wind. Plankton primary production is co-limited by phosphorus and nitrogen, and is highest in the inner part of the lagoon, due to the combined effects of high water residence time and high nutrient inputs from the boundary. However, a sensitivity analysis highlights the importance of exchanges with the Mediterranean Sea in maintaining a high level of productivity. Intensive use of fertilizers in the catchment area has a significant effect on phytoplankton biomass increase. Graphical abstract: Highlights: A 3D coupled hydrodynamic-biogeochemical model in a Mediterranean lagoon Annual water budget using the hydrodynamic model presented Time and spatial variation of phytoplankton biomass influenced by meteorology Phytoplankton growth is limited by phosphorus and nitrogen depending on season Quantification of annual fluxes of nitrogen among ecosystem components